2015
DOI: 10.1039/c5ra04708k
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical polymorphic MnCO3 series induced by cobalt doping via a one-pot hydrothermal route for CO catalytic oxidation

Abstract: In this study, a series of cobalt-doped MnCO 3 hierarchical microstructures with different morphologies were synthesized by tuning a single variable (the dopant content) via a one-step, mild solvothermal synthesis in a N,N-dimethylformamide (DMF) solution system. Structure evolution of the polymorphic MnCO 3 took place with the morphology obviously transforming from an initial flower-microstructure to fan-like, then to hedgehog-like hemispheres and finally to flake-spheres as the Co 2+ theoretical content (Co/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…So far, MnCO 3 materials have been successfully synthesized by precipitation, 12,14 hydrothermal methods, 8,20 ionic liquid-assisted hydrothermal synthesis, 23 chelate mediated growth, 9 and electrodeposition. 18 In order to improve the lithium storage properties, MnCO 3 samples containing hollow microspheres and nanocubes, 14 hierarchically architectured microdumbbells and lamellar-structured nanosheets, 17 mesoporous single crystals, 18 submicron peanuts, 19 ellipsoids and twinborn spheres, 20 flake-spheres 24 and steep rhombohedra microcrystals 25 have been prepared and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…So far, MnCO 3 materials have been successfully synthesized by precipitation, 12,14 hydrothermal methods, 8,20 ionic liquid-assisted hydrothermal synthesis, 23 chelate mediated growth, 9 and electrodeposition. 18 In order to improve the lithium storage properties, MnCO 3 samples containing hollow microspheres and nanocubes, 14 hierarchically architectured microdumbbells and lamellar-structured nanosheets, 17 mesoporous single crystals, 18 submicron peanuts, 19 ellipsoids and twinborn spheres, 20 flake-spheres 24 and steep rhombohedra microcrystals 25 have been prepared and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…2b-d, the sizes of the Mn-ZSM-5 samples become larger (4-6 mm) with the content of Mn-doping, as a result of the growth acceleration of ZSM-5 via impurities (Mn ions). 41 The compositional data of the as prepared P 0 -P 1 samples are shown in Table 1. As the SiO 2 /Al 2 O 3 ratio increases, the Mn/(Si + Mn) atom ratio increases and the theoretical doping increases, indicating that Mn x+ substitutes Al 3+ into the ZSM-5 lattice and thus drives the formation of a stable MFI structure.…”
Section: Morphology and Structural Analysismentioning
confidence: 99%
“…The decreased diameters of the Mn 2 O 3 nanowires reveal that the cobalt and nickel ions have played a pivotal role during the growth process of the Mn 2 O 3 . In fact, both Co 2+ (0.072 nm) and Ni 2+ (0.069 nm) ions can accelerate the crystal nucleation rate, 27 leading shorter time for maturity, resulting in the decreased size. Inductively coupled plasma (ICP) analysis indicated that the molar ratio of doping ions in Mn 2 O 3 nanostructures are 1.34% for Ni-doped Mn 2 O 3 , which is lower than theoretical doping and 4.95% for Co-doped Mn 2 O 3 , which is close to the initial reactant composition (Table 1 in ESI †).…”
Section: Characteristics Of Nanowiresmentioning
confidence: 99%
“…[16][17][18] As is known, the shape-selective synthesis of Mn 2 O 3 nanostructures is demonstrated to be a powerful method to promote their catalytic performance. 27 Generally, surface oxygen vacancies promote high dispersion and strong anchoring of transition metal ions on the metal oxides surface. 19 It is well known that cation substitution can provide an effective tool for tailoring the physicochemical properties of metal oxides, 20,21 in which case the functionalities of Mn 2 O 3 nanomaterials can be optimized by goal-directed control of the cation composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation